Antioxidant capacity, antitopoisomerase activity and secondary metabolites identification in extracts of Cherimoya pulp (Annona cherimola Mill) - Razura-Carmona, F. F.; Montalvo-González, E.; Ramírez-Mares, M. V.; Bueno-Durán, A. Y.; Sáyago-Ayerdi, S. G.; Zamora Gasga, V. M.; Sánchez-Burgos, J. A. (Revista Bio Ciencias, 2021)
Annonaceae, like Annona cherimola Mill., are recognized by alternative medicine for their therapeutic properties, but little is known about the compounds that can provide such activity. Because the edible portion of this fruit is the pulp, in this work the antioxidant capacity was evaluated through an organic aqueous extraction and the antitopoisomerase activity in ethanol (ME) and ethyl acetate (MA) extracts of cherimoya pulp lyophilized, finally the active extract was characterized by gas chromatography coupled to masses (GC/MS). The cherimoya pulp showed a concentration of total soluble phenols (TSP) of 145.5713 mg GAE / g, in the ABTS▪ + assay (128.6991 µg TE/g) and in the FRAP assay (43.7257 mM TE/g). We proved that MA extract inhibits the clonal expansion of a mutant of Saccharomyces cerevisiae by inhibition of topoisomerase I (22 %). The characterization of the MA extract by GC/MS revealed the presence of two diterpenes of the family of Kaurenes (kauran-15-ol and kauran-16-ol) and gummiferolic acid, which have demonstrated antiproliferative activity through the inhibition of topoisomerases in other studies. In this way, it was possible to elucidate a probable mechanism through which the pulp of this fruit has a healthy effect due to its antioxidant capacity and the presence of secondary metabolites with the capacity of inhibit the topoisomerase I activity.